IL-1 and its role in rat carrageenan pleurisy - R. Goodman; L. R. Mantegna; C. L. McAIlister; E. Bruin; R. L. Dowling; H. George; W. Feeser; B. Freimark; M. Lischwe; S. Pick; R. R. Harris; J. S. Kerr (Hindawi Limited, 1993)
The carrageenan pleurisy model, which is characterized by cellular influx and oedema, has been used to examine the effects of anti-inflammatory compounds such as naproxen. Interleukin-1α and β (IL-1) are known to be pro-inflammatory mediators, and their roles in this model are unknown. Intrapleural injection of 1% viscarin carrageenan or saline was administered to male Lewis rats. Four to 24 h later, cell counts, fluid volumes and IL-1β levels (measured by ELISA) were determined in the pleural cavity. Serum corticosterone levels were measured only at 4 h. Significant increases in IL-1β levels precede cell influx suggesting IL-1β plays a role in the maintenance of cell accumulation in the pleural cavity. None of the drugs tested, including the IL-1 receptor antagonist, maintained pleural cell influx and IL-1β levels at control levels. When human IL-1α or β or rat IL-1β were injected individually into the pleural cavity, none of these cytokines were pro-inflammatory, as measured by increased cell influx and fluid extravasation. These results suggest that although IL-1β levels increase in the pleural cavity in response to carrageenan, IL-1 per se is not the initiator of the pro-inflammatory events of cell influx and oedema in this model.